PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENGEMBANGAN DIRI SISWA KELAS XI SMA NEGERI 2 BINJAI - Hadi Widodo; Budi Febrian (Jurnal Al-Fatih, 2018)
This research aims to find out if there is a signifikn between the influence of counselling group against the personality of the student. The problem in this research is whether there is a significant influence of the tutoring service group towards the development of students ' self. This research uses a quantitative approach to the technique of korelasional. The population of this research are all students of SMA Negeri 2 Binjai, sampled in this study are students of Class XI SMA Negeri 2 Binjai, a total of 72 people. The instruments used are the now, the data analyzed by Product Momment Correlation. Based on the results of research that has been done, then the research can be inferred the existence of a variable group tutoring service influence towards the development of students ' self of 0.963.